O bloqueio de proposições na arena legislativa e a relação executivo x legislativo no Brasil - Elaine da Silva Gontijo (2017)
This paper analyzes the relationship between the Executive and Legislative Powers within the scope of legislative activity in Brazil. Unlike other papers, which generally measure the Executive's preponderance by observing the constitutional prerogatives that allow the president to exercise his agenda power in the National Congress, my effort was to analyze the proposals originated by the parliamentarians and the need for the president, with the support of its parliamentary base, to use the available regimental instruments to prevent certain bills from being approved. The argument is that it is not possible to evaluate the success of the president in the legislative arena observing only the approval of the proposals that he originates. The analysis of the legislative success of the Executive requires analyzing the whole of its work in the National Congress, including the proposals presented by parliamentarians, who tend to change the public policies implemented by the government and demand from the president the reinforcement of its Negative Agenda Power. By the analysis of the use of blocking mechanisms in propositions of government interest, specifically the Ministry of Education, in the Education and Finance and Taxation Committees of the Chamber of Deputies, presented by parliamentarians from 1995 to 2014, the study Allows to affirm that the Executive Power, using an institutional arrangement constituted by party leaderships, Parliamentary Advisories of the Ministries and internal institutions to the presidential cabinet, interferes in the processing of the bills presented by the members of the Legislative Power.